Indovina Chi: identità contemporanee da ri-conoscere - Sarra, Giada (SocietàMutamentoPolitica, 2013)
What the identity is, in which form it is declined, through which paths of re-cognition it operates and how sociolog y is supposed to begin to reconsider it are the themes of this critical note, developed analysing three sociological studies.